Quantification of Lactobacillus spp. and Bifidobacterium spp. in hospitalized children with Pierre Robin Sequence - Vieira, Narciso Almeida; Dalben, Gisele da Silva; Cestari, Beatriz Pereira; Talarico, Silvia Toledo; Taddei, Carla R. (O Mundo da Saúde, 2024)
Objective: To detect and quantify Bifidobacterium spp. and Lactobacillus spp. in the intestinal microbiota (IM) of children with Pierre Robin sequence (PRS) during the first and second months of life, and to verify possible influences on the definitive establishment of the IM. Design: Longitudinal, descriptive study. Setting: Tertiary cleft care center. Participants: Six children, one male and five females, who were hospitalized for the management of their condition, were evaluated during the first (M1) and second (M2) months of life. Interventions: Fecal samples were collected and analyzed through DNA extraction for the quantification of anaerobic genera Bifidobacterium spp. and Lactobacillus spp. Socioeconomic and clinical data on the children were also collected. Main outcome measures: The number of copies of bacterial species was calculated for each fecal sample. Results: The genus Bifidobacterium was present in all children analyzed, with a significant increase at M2 for five children. The number of copies per gram of feces ranged from 1.8 × 10⁷ to 5.5 × 10¹¹ at M1 and from 4.2 × 108 to 3.0 × 10¹² at M2. The genus Lactobacillus sp. was not present in all children, being detected in low quantities, with averages ranging from 8.5 × 10³ to 9.7 × 108 copies per gram of feces at M1. At M2, only one child presented a quantification of 8.1 × 104 , while two other children showed an absence of the microorganism at both M1 and M2. Conclusions: The bacterial colonization of the gastrointestinal tract of children with PRS is influenced by specific clinical and environmental factors. A healthy intestinal microbiota is essential for the development and immunity of newborns, but PRS-associated challenges affect microbiota diversity.